Optimalisasi Perencanaan Pondasi Rakit pada Bangunan Pendidikan Tinggi - Muchti, Hafizh Adha; Mazni, Deni Irda; Herman, Hazmal; Boy, Wendi (Universitas Andalas, 2024)
This study aims to determine the right type of foundation in the construction of higher education buildings, with a focus on the planning of raft foundations. This study includes the calculation of soil bearing capacity, planning of foundation dimensions and reinforcement, analysis of settlement and uplift, and cost estimation. The methodology used follows the SNI standard, HSP Quarter II of Padang City, and uses ETABS software. Analysis of soil bearing capacity is carried out based on the Meyerhof method using Microsoft Excel, while the loading is analyzed through ETABS. The results of the study indicate that the raft foundation planned for Building C of Dharma Andalas University is able to withstand existing soil tension of 9.755 t/m², which is below the permitted bearing capacity of 39.169 t/m². This foundation is designed with a thickness of 450 mm, using D13 mm threaded reinforcement with a distance of 200 mm and 250 mm. The planned sloof dimensions are 40 cm x 80 cm with 20D22 mm main reinforcement and D10 mm stirrups. The settlement analysis shows a value of 46.997 mm, which still meets the permit limit of 100 mm. The estimated total cost of building a raft foundation, including 11% VAT, is Rp1,673,300,000.00. Based on these results, the planned raft foundation is declared capable of withstanding the load on existing soil conditions and meets the permit stress requirements. This study recommends further exploration of the application of raft foundations on different types of soil and the development of alternative designs for simpler construction.